2016
DOI: 10.15654/tpk-140962
|View full text |Cite
|
Sign up to set email alerts
|

Prävalenz von Antikörpern gegen Borrelia burgdorferi, Anaplasma phagocytophilum und bestimmte Leptospira-interrogans-Serovare bei Berner Sennenhunden

Abstract: BMD had a higher prevalence of anti-Bbsl, anti-L. copenhageni and anti-Ap antibodies than control dogs. Significantly higher antibody titers against L. canicola (p = 0.003), L. copenhageni (p = 0.005), L. grippothyphosa (p = 0.029) and L. vanderhoedoni (p = 0.035) were seen in BMD compared with control dogs, but the reason for this and potential clinical implications are not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In Europe, Anaplasma spp. seroprevalence has been reported in almost all countries with rates ranging from 1.1 to 56.5% ( 143 , 148 , 150 , 183 , 190 ). The detection of A. phagocytophilum DNA has also been reported mostly from central and northern countries ( Table 1 ) with prevalence rates up to 14.2% ( 174 ).…”
Section: Distribution and Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 99%
“…In Europe, Anaplasma spp. seroprevalence has been reported in almost all countries with rates ranging from 1.1 to 56.5% ( 143 , 148 , 150 , 183 , 190 ). The detection of A. phagocytophilum DNA has also been reported mostly from central and northern countries ( Table 1 ) with prevalence rates up to 14.2% ( 174 ).…”
Section: Distribution and Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 99%
“…This dog breed seems to have a predisposition for B. burgdorferi s.l. infection, as demonstrated by several studies (97)(98)(99), although the reasons for this predisposition are unknown (58). As reported above, a significant effect of the utilized diagnostic test on the seroprevalence in dogs was found (section Tick-Borne Encephalitis Virus, Supplementary Figure 1), with lower rates determined by the most recently developed test, a C6-based rapid ELISA, than by conventional ELISA or IFAT (57).…”
Section: Dogs and Catsmentioning
confidence: 68%
“…The clinical data and laboratory test results were derived from data collected for another study with prospectively enrolled dogs [ 15 ]. Apart from the published results, additional data was collected and additional laboratory tests were performed for the study that have not yet been analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies revealed a significantly higher prevalence of antibodies to B. burgdorferi sensu lato and to Anaplasma (A.) phagocytophilum in BMDs than in control dogs indicating a higher infection prevalence [ 14 , 15 ]. Chronic persistent infections, such as with B. burgdorferi sensu lato, Ehrlichia spp., and Anaplasma spp.…”
Section: Introductionmentioning
confidence: 99%